Reduction of ammonia emissions by using a urease inhibitor in a mechanically ventilated dairy housing system. (April 2021) - Bobrowski, Anna B.; van Dooren, Hendrik Jan; Ogink, Nico; Hagenkamp-Korth, Frauke; Hasler, Mario; Hartung, Eberhard
Abstract : Ammonia emissions have a negative influence on both human and animal health as well as on the environment. Livestock farming, in particular the dairy sector, is a major source of ammonia emissions. Urease inhibitors may act as a suitable mitigation measure without requiring the high investments connected with, e.g., new floor surfaces in barn refurbishments. The main aim of this field study was to a) quantify the reduction potential of the urease inhibitor K and b) provide information on the chronological reduction response of the inhibitor. The experimental setup was based on an in time and a case–control approach, according to the requirements of the Verification of Environmental Technologies for Agricultural Production test protocol. The investigations were carried out in two mechanically-ventilated units of the Leeuwarden Dairy Campus. Both sets of investigations were performed over all seasons. A new liquid chemical formulation of the urease inhibitor K, was applied at a rate of 2.5 mg m −2 when mixed with 50 ml m −2 water. Urease activity was measured to confirm the reduction potential of the inhibitor. The in time approach found a seasonal reduction potential, where ammonia emissions were reduced by 17–23% in summer, 10–31% in winter and 22% in spring. The case–control approach found a reduction pattern with the highest reduction potential at the 16-h time slot. However, the time slot analysis found a decrease in reduction after the inhibition peak. Highlights: Based on the VERA protocol, an in time and a case–control approach were realised. First determination of the chronological reduction process under field conditions. NH3 reduction potential of 17% up to 31% could be observed over all seasons. Urease inhibitors proved to be a feasible and adaptable mitigation measure.